Individual patient-centered target-driven intervention to improve clinical outcomes of diabetes, health literacy, and self-care practices in Nepal: A randomized controlled trial - Pardhan, Shahina; Upadhyaya, Tirthalal; Smith, Lee; Sharma, Tara; Tuladhar, Sarita; Adhikari, Bhojraj; Kidd, John; Sapkota, Raju (Frontiers in Endocrinology, 2023)
Purpose:To examine the effectiveness of a culturally and linguistically appropriate, patient-centered, target-driven lifestyle intervention with video education training in improving clinical outcomes, health literacy, and diabetic self-care practices in newly diagnosed patients in Nepal. Methods:A total of 110 participants with newly and consequently diagnosed Type 2 were randomly allocated into intervention (mean age=45±9.7years) and control (mean age=47±12.5years) groups. Intervention group participants were trained on a culturally and linguistically appropriate diabetic video education program and were given a customized dietary and physical activity plan with specific targets to practice at home. Participants’ compliance was monitored weekly via telephone calls. Both groups received the usual treatment from their doctor and were followed up after three months. Outcome measures included changes in: i.diabetic health literacy, diet, and physical activity measured using self-reported questionnaires; and ii.blood glucose (glycated hemoglobin, HbA1c), cholesterol, blood pressure, body mass index, and visual acuity. Clinical outcome measures were blinded from randomization and intervention allocation. Results:After three months, HbA1c decreased to 6.1% from the baseline value of 7.2% in the intervention group compared to 6.6% in the control group from the baseline value of 7.1% (p<0.05). The intervention group had mean total cholesterol and low-density lipoprotein of 174 and 95.5 mg/dL, which were significantly lower than 186 and 107.5 mg/dL in the control group. Daily white rice consumption decreased by 36.5% in the intervention vs. 4% in the control group (p<0.05). After three months, the intervention group exercised more than the control group (p<0.05). All intervention group participants self-initiated retinal screening among which 13% showed early diabetic retinopathy signs compared to 0% in the control group. Health literacy improvement in the intervention group was found to be sustained after three months too. Conclusions:A culturally appropriate, target-driven lifestyle intervention with video education training is effective in improving clinical outcomes, health literacy, and self-care practice in newly diagnosed diabetic patients in Nepal, i.e., at a time period when effective diabetes control is vital to prevent further complications. The training intervention could be rolled out nationwide in order to reduce the risk of diabetic-related complications and improve people’s quality of life and productivity.